2023
DOI: 10.1002/ardp.202300216
|View full text |Cite
|
Sign up to set email alerts
|

Greenness‐by‐design approach for developing novel UV spectrophotometric methodologies resolving a quaternary overlapping mixture

Abstract: Greenness-by-design (GbD) is an approach that integrates green chemistry principles into the method development stage of analytical processes, aiming to reduce their environmental impact. In this work, we applied GbD to a novel univariate double divisor corrected amplitude (DDCA) method that can resolve a quaternary pharmaceutical mixture in a fixed-dose polypill product. We also used a genetic algorithm as a chemometric modeling technique to select the informative variables for the analysis of the overlapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(61 reference statements)
1
2
0
Order By: Relevance
“…The current study extends our previous work [ 19 ] on the conceptualization of the GbD approach for UV spectrophotometric methods development. Through the current work, we illustrated the photochemical quantum phenomena that affect the UV peak broadening and the degree of interference of different compounds in different solvents besides demonstrating how GbD can optimize the solvation effect to control the peak broadening of the UV spectrum of each compound from the photochemical quantum perspective.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The current study extends our previous work [ 19 ] on the conceptualization of the GbD approach for UV spectrophotometric methods development. Through the current work, we illustrated the photochemical quantum phenomena that affect the UV peak broadening and the degree of interference of different compounds in different solvents besides demonstrating how GbD can optimize the solvation effect to control the peak broadening of the UV spectrum of each compound from the photochemical quantum perspective.…”
Section: Resultssupporting
confidence: 81%
“…Building on our previous work [ 19 ] we concluded that the type of the utilized solvent directly affects the morphology of the resulting UV spectrum of the scanned compound. Several factors play roles in this phenomenon as hydrogen bonding (HB) between the solvent and the solute molecules, the polarity of the solvent and its effect on the excitation states of the compound and spin multiplicity of the solute molecule itself.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation